The Effects of Working from Abroad on Employees : the case of Accenture in Czech Republic - Seitkhan, Akezhan; Orel, Marko, 1986-; Hron, Michal; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
The pandemic has given a push to the concept of telework, which has been used by many companies already but has accelerated with the pandemic forcing employees to Work-From-Home. However, there is a new concept of Working-From-Anywhere that is taking shape because people feel tamed by the borders of working in one country whilst having the necessary equipment to work anywhere. The particular arrangement has been implemented by Accenture, who are testing the International Remote Working Pilot (IRWP) on employees. The 10 Accenture (Czech Republic) employees availing for the IRWP have been chosen for semi-structured interviews before and after the WFA, and at the same time, for monitoring the changes in their well-being, they were asked to make diary logs to predetermined questions that were answered during the period of IRWP. The goal is to identify the perceived benefits of the WFA arrangement by Accenture employees and check the implications on well-being and other aspects related to work. The results illustrated that WFA positively affects employees as they had the chance to meet their family and friends or travel to new countries, whilst the drawbacks like time difference affect employees only at the beginning. Furthermore, it turned out that the productivity is the same for most employees, who need some time in the beginning due to the adaptation period as the new environment temporarily persists. In summary, all employees were incredibly proud to work for the company that offers such benefits that are critical for them, which is beneficial for employees and the companies who would have much more motivated and satisfied employees who can concentrate on work.
Vedoucí práce: Marko Orel
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses